Design and Development Of Automatic Health Monitoring System Ganugapaty Mythili1, M.Bala Subrahmanyam2, T.Ramaiah3 - et. al, Ganugapaty Mythili (International Journal of Advanced Science and Technology, 2020)
In this paper the design and development of automatic Patient Health Monitoring System is implemented. Here when there will be variation in the heart beat then the heart beat sensor will detect automatically and sends an SMS to the corresponding member. In the same way when the temperature sensor will be exceeded then the location of that place is detected automatically. The entire system is controlled by the ARM. The buzzer will be used as an indication when it is needed. The doors of window will be opened automatically when the temperature of room will be exceeded. Hence this project gives effective result.